2018
DOI: 10.1002/2017jd027247
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Shortwave Direct Aerosol Radiative Forcing Using CALIOP and MODIS Observations

Abstract: In this study, all‐sky ShortWave Direct Aerosol Radiative Forcing (SWDARF) at the top of atmosphere is estimated using the method of Oikawa et al. (2013) applied to two generations of Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) Level 2 products, i.e., version 2 (V2) and version 3 (V3), and the Moderate Resolution Imaging Spectroradiometer (MODIS) cloud product. The estimated SWDARF in Oikawa et al. (2013) was based on CALIPSO V2 product, which contained significant errors in cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 66 publications
4
27
1
Order By: Relevance
“…Determining these spectral dependencies is often achieved or complemented by the identification of the aerosol type (dust, sea salt, etc.) which then determines the spectral shapes from a predetermined aerosol optical model (e.g., Loeb and Su 2010;Henderson et al 2013;Oikawa et al 2013;Matus et al 2015;Kato et al 2018). Generalizing the uncertainty associated with this approach is difficult since it would involved determining the accuracy of each specific method of aerosol typing and the aerosol optical models.…”
Section: B Spectral Simplificationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Determining these spectral dependencies is often achieved or complemented by the identification of the aerosol type (dust, sea salt, etc.) which then determines the spectral shapes from a predetermined aerosol optical model (e.g., Loeb and Su 2010;Henderson et al 2013;Oikawa et al 2013;Matus et al 2015;Kato et al 2018). Generalizing the uncertainty associated with this approach is difficult since it would involved determining the accuracy of each specific method of aerosol typing and the aerosol optical models.…”
Section: B Spectral Simplificationsmentioning
confidence: 99%
“…This conclusion is even more strongly supported by studies that have made CALIPSO-based DRE estimates. Oikawa et al (2018) showed that the magnitude of the aerosol DRE is about a factor of 7 larger in instances of aerosol below cloud rather than when aerosol is above cloud (their Table 2). The aerosol DRE from Matus et al (2015) was larger by a factor of 12 in magnitude in columns with thin cloud (COD , 1) than those with thick cloud (COD .…”
Section: Scene Typementioning
confidence: 99%
See 3 more Smart Citations